TMIC-57. PRO-TUMORAL EFFECTS OF INTRA-TUMORAL NEUTROPHILS IN THE GLIOBLASTOMA MICROENVIRONMENT. (11th November 2019) - Shah, Sumedh; Yagnik, Garima; Nguyen, Alan; Wadhwa, Harsh; Spatz, Jordan; Safaee, Michael; Cheng, Justin; Aghi, Manish
Abstract: While macrophage enrichment and lymphocyte depletion have been described in glioblastoma, intratumoral neutrophils and their effect on glioblastoma have been under-characterized. While tumor-associated neutrophils (TANs) were initially regarded as passive bystanders due to their short-lived nature, investigation of TANs in other cancer types revealed pro-tumoral roles. Therefore, we sought to characterize TANs in the glioblastoma microenvironment using transcriptomic analysis and define their oncologic effects. Flow cytometric analysis of patient samples for neutrophils (CD11b+/CD15+/CD66b+) revealed higher percentages of TANs in glioblastoma compared to low-grade gliomas (1.76% [n=13] vs. 0.33% [n=6], p=0.03). Using the Transwell migration assay with glioblastoma tumor conditioned-media (CM), we found that recruitment of circulating neutrophils to tumor sites is mediated by leukotriene-B4 chemoattraction and that this interaction can be blocked with the addition of LtB4 receptor antagonist, LY293111. TANs were morphologically activated, unlike circulating neutrophils from GBM patients (P< 0.05) and, while not intravascular, were close to blood vessels. We performed single-cell RNA sequencing of isolated TANs and found a distinct transcriptomic profile relative to circulating neutrophils from these patients, particularly upregulated osteopontin. Osteopontin concentration was significantly higher in TAN CM than in patient-matched peripheral blood neutrophil CM (3.2ng/mL [n=3] vs. 0.02ng/mL [n=3], p< 0.05). Because osteopontin is linked to GBM stem cell-like phenotype maintenance and TANs localized to the perivascular niche where GBM stem cells reside, we investigated TAN-GBM stem cell interactions and osteopontin as a potential mediator. We found TAN CM increased proliferation and stem cell markers (Nanog, Oct4, Sox2) of stem cell-containing GBM neurospheres (p< 0.01). These effects were blocked by osteopontin-neutralizing antibodies (p< 0.01). Our work defines neutrophil-mediated pro-tumoral effects and their mechanisms and identifies a novel approach to target GBM stem cells—by disrupting the immune cell mediators that create their supportive microenvironment in the perivascular niche.